Increased number and frequency of group 3 innate lymphoid cells in nonlesional psoriatic skin. (March 2014) - Dyring‐Andersen, B.; Geisler, C.; Agerbeck, C.; Lauritsen, J.P.H.; Gúdjonsdottir, S.D.; Skov, L.; Bonefeld, C.M.
<x xml:space="preserve">Abstract</x> What's already known about this topic? The interleukin (IL)‐23/Th17 axis is important for the pathogenesis of psoriasis. Innate lymphoid cells producing IL‐17 and/or IL‐22 are known to be involved in the pathogenesis of psoriasis. What does this study add? An increased frequency of group 3 innate lymphoid cells is found in noninvolved psoriatic skin compared with healthy skin, which may indicate that these cells contribute to psoriasis development.